(untitled) (Foundations in Clinical Pharmacy Practice, 2025)
Author Dr. Nitin Ambati, PG Medico, Illinois, Saint James School of Medicine, Chicago, United States Abstract Acute care pharmacy practice addresses complex medication needs in hospitalized patients through specialized knowledge, rapid intervention, and interdisciplinary collaboration across diverse clinical environments. Critical care pharmacotherapy optimizes life-sustaining medications including vasopressors, antimicrobials, sedatives, and nutrition support through precise pharmacokinetic dosing, advanced monitoring, and pathophysiologic-based decision-making in critically ill patients. Emergency medicine services provide time-sensitive medication management for trauma, cardiovascular emergencies, toxicological exposures, and acute exacerbations requiring rapid assessment, prioritization, and intervention coordination. Internal medicine practice addresses complex multimorbidity through comprehensive medication management, transitions of care coordination, and antimicrobial stewardship integrating evidence-based approaches with patient-specific factors. Surgical care management encompasses perioperative medication optimization, antimicrobial prophylaxis, thromboembolism prevention, and enhanced recovery protocols promoting favorable surgical outcomes while preventing complications. Pain management strategies implement multimodal analgesia, opioid stewardship, and patient-specific approaches addressing acute, chronic, and procedural pain through appropriate medication selection, administration techniques, and monitoring protocols. This specialized practice area requires advanced clinical knowledge, rapid decision-making, and effective interdisciplinary communication to optimize medication therapy in acutely ill patients. Keywords: Hospital Pharmacy Practice, Critical Illness Pharmacotherapy, Perioperative Medication Management, Antimicrobial Stewardship, Emergency Pharmaceutical Care VIEW PDF